The Five Focusing Steps of the Theory of Constraints: Problems of Application in Strategic Analysis - I. A. Nechitaylo (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
Objectives. We identify and investigate circumstances that limit an application of the Five Focusing Steps of the Theory of Constraints in the strategic analysis of investment projects effectiveness.Methods. The methods of factor analysis and financial mathematics including methods for evaluation real options are used.Results. It is shown that in some cases, an increase in business value can be created only by a combination of a number of investment projects, leading to consistent removal of constraints and arising of useful synergistic effects. It is also shown that a value of a project can be determined by changes in the strategy that the company will have the opportunity to make if project is implemented. In such cases, their evaluation without taking into account subsequent decisions may distort their true value.Conclusions and Relevance. We concluded that the main object of evaluation in strategic analysis should be a strategy as a series of future transformations, taking into account the real options generated by them. Therefore, the evaluation of single projects on the base of the Theory of Constraints can lead the rejection of valuable projects due to distortion of their true value. At the same time an application of the Five Focusing Steps in strategic analysis protect against investment in projects with negative net present value.